2016
DOI: 10.1099/ijsem.0.000689
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus wasatchensis sp. nov., a non-starter lactic acid bacteria isolated from aged Cheddar cheese

Abstract: T could only utilize one of the 50 substrates tested, ribose, although it does slowly utilize galactose. In the API ZYM system, strain WDC04 T was positive for leucine arylamidase, valine arylamidase, cysteine arylamidase (weakly), naphthol-AS-BIphosphohydrolase and b-galactosidase activities. Total genomic DNA was sequenced from strain WDC04 T using a whole-genome shotgun strategy on a 454 GS Titanium pyrosequencer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…We also examined enzymatic characteristics of strain 11-1 using the Api Zym test and compared them with those of other related strains (Curk et al, 1996; Oberg et al, 2016) (Table 4). The enzymatic characteristics data of L. paraplantarum are unavailable, and therefore we compared the data of strain 11-1 and control strain L. plantarum JCM 1057, and previously reported data of L. plantarum and L. curvatus .…”
Section: Resultsmentioning
confidence: 99%
“…We also examined enzymatic characteristics of strain 11-1 using the Api Zym test and compared them with those of other related strains (Curk et al, 1996; Oberg et al, 2016) (Table 4). The enzymatic characteristics data of L. paraplantarum are unavailable, and therefore we compared the data of strain 11-1 and control strain L. plantarum JCM 1057, and previously reported data of L. plantarum and L. curvatus .…”
Section: Resultsmentioning
confidence: 99%
“…The bacteria with different morphology were isolated and 23 strains were selected. Additionally, each strain was evaluated for catalase activity, peroxidase activity, microscopy morphology (Axiolab, Carl Zeiss Jena Germany), and Gram stain following the procedure described by Oberg et al (2016).…”
Section: Isolation Of Lactic Acid Bacteriamentioning
confidence: 99%
“…It was recently reported that a new species of nonstarter lactic acid bacteria (NSLAB) was isolated from cheese and implicated in unwanted gas formation during the storage of Cheddar cheese (Ortakci et al, 2015b,c). This obligatory heterofermentative (OHF) lactobacillus was designated as Lactobacillus wasatchensis (Oberg et al, 2016); it co-utilizes ribose and galactose (Ortakci et al, 2015a) to support growth, and produces CO 2 when 6-carbon sugars are present and utilized for energy production. The following risk factors for unwanted gas production and formation of splits and cracks during storage of Cheddar cheese were identified:…”
Section: Hot Topicmentioning
confidence: 99%
“…(2) it requires the medium to be supplemented with a 5-carbon sugar such as ribose for growth; and (3) its preferred temperature for growth is ~23°C, with Hot topic: Geographical distribution and strain diversity of Lactobacillus wasatchensis isolated from cheese with unwanted gas formation 8765 only marginal growth at 37°C (the typical incubation temperature used for enumerating NSLAB; Oberg et al, 2016). The current method for enumerating Lb.…”
Section: Hot Topicmentioning
confidence: 99%
See 1 more Smart Citation